Inovaç\~oes Democráticas na América Latina; Democratic innovations in Latin America - Thamy Pogrebinschi; Melisa Ross (Revista Debates, 2021)
Este artigo objetiva elucidar a rica diversidade de contextos sobrepostos e narrativas singulares que comp\~oem o cenário da inovaç\~ao democrática na América Latina. Para isso, examinaremos o contexto e as principais tendências das inovaç\~oes democráticas em cada uma das sub-regi\~oes, a saber, o Cone Sul, a América Central e os Andes. Esta análise é complementada por exemplos emblemáticos de inovaç\~oes democráticas em 18 países. Por fim, realizamos uma breve avaliaç\~ao de experimentos participativos da sociedade civil em resposta à pandemia de Covid-19 em 2020 e das implicaç\~oes da crise sanitária no campo da participaç\~ao cidad\~a no continente. Na conclus\~ao, apontaremos alguns rumos no desenvolvimento de inovaç\~oes democráticas na América Latina e tentaremos extrair algumas liç\~oes. – – This article aims to elucidate the rich diversity of overlapping contexts and unique narratives that compose the scenario of democratic innovations in Latin America. To this regard, we will examine the main context and general trends of democratic innovations in each of the sub-regions, namely, the Southern Cone, Central America and the Andes. This analysis is complemented by examples of emblematic democratic innovations and representative cases of social participation in 18 countries. Finally, we conducted a brief assessment of civil society participatory initiatives in response to the Covid-19 pandemic in 2020 and the implications of the health crisis in the field of citizen participation on the continent. In conclusion, we will point out some directions in the development of democratic innovations in Latin America and attempt to draw some lessons.
Keywords: 300; inovaç\~oes democráticas; América Latina; participaç\~ao social; Covid-19; democratic innovations; Latin America; social participation